Safety and efficacy of betaine anhydrous for food‐producing animal species based on a dossier submitted by AB Vista. (12th July 2018) - ; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of betaine anhydrous produced ■■■■■ as a nutritional additive to be used in feed for all food‐producing animal species except rabbits. Glycine betaine (betaine) acts as a methyl group donor in transmethylation reactions in organisms. Betaine occurs in numerous tissues of vertebrates as an osmolyte ensuring osmoprotection. Betaine anhydrous (97%, 96% or 91%) is considered safe for the target species at a maximum supplementation rate of 2, 000 mg betaine/kg complete feed. The use of betaine anhydrous (97%, 96% and 91%) as a feed additive up to a supplementation of 2, 000 mg/kg complete feed does not pose concerns to consumer safety. The betaine liquid product contains a high proportion of unknown material (about 30% on dry matter basis). The FEEDAP Panel therefore cannot conclude on the safety of the liquid form of the additive for the target species and the consumer. In the absence of data, the FEEDAP Panel cannot conclude on the safety for the user. The supplementation of feed with betaine anhydrous does not pose a risk to the environment. Betaine has a potential to become efficacious in food‐producing animal species and categories when administered via feed, especially when methyl groups from methionine or choline are limiting. The FEEDAP Panel made a recommendation on the use of the additive in premixtures without choline chloride.